2015
DOI: 10.1186/s13068-015-0298-8
|View full text |Cite
|
Sign up to set email alerts
|

Xpp1 regulates the expression of xylanases, but not of cellulases in Trichoderma reesei

Abstract: BackgroundThe ascomycete Trichoderma reesei is industrially used for the production of cellulases. During the production process xylanases are co-secreted, which uses energy and nutrients. Cellulases and xylanases share the same main regulators, which makes a knowledge-based strain design difficult. However, previously a cis-element in the promoter of the main xylanase-encoding gene was identified as binding site for a putative repressor. Subsequently, three candidate repressors were identified in a pull-down … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 33 publications
3
50
0
2
Order By: Relevance
“…Previously, the expression of Xpp1 itself was shown to depend on growth rate (33). Taken together, we propose that the general role of Xpp1 is to direct the flow of material and energy toward the accumulation of biomass.…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…Previously, the expression of Xpp1 itself was shown to depend on growth rate (33). Taken together, we propose that the general role of Xpp1 is to direct the flow of material and energy toward the accumulation of biomass.…”
Section: Discussionsupporting
confidence: 60%
“…The pigment is a mixture of different sorbicillin derivatives, of which biosynthesis results from a gene cluster that is present in a range of not closely related ascomycetes (38,39). However, in a previous study, we cultivated an xpp1 deletion strain and its parent strain on carboxymethylcellulose (CMC) to determine the expression levels of cellulases (33). Throughout growth, we observed that cultures of the xpp1 deletion strain turned yellow earlier and that coloring was more pronounced compared with the parent strain.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations